1986
DOI: 10.1210/endo-118-3-1011
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Mouse Uterine Epithelial Cellsin Vitro

Abstract: Although estrogens can stimulate the growth of uterine epithelial cells in vivo, there is no clear effect of estrogens on the in vitro growth of epithelial cells from reproductive tract tissues; thus, we have established a defined culture system for mouse uterine epithelial cells. Pieces of uteri from immature CD-1 mice (21-23 days of age) were treated with trypsin, and the epithelial fragments were separated, enriched by Percoll gradient centrifugation, and seeded on collagen gels prepared from rat tail tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
1
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(69 citation statements)
references
References 24 publications
7
60
1
1
Order By: Relevance
“…In female fetuses, however, primary and essential factors which regulate cell proliferation and differentiation of the Müllerian duct have not yet been identified either in vitro or in vivo. EGF and insulin-like growth factor (IGF)-I stimulate cell proliferation in immature mouse uterine and vaginal epithelial cells in vitro (Tomooka et al 1986, Iguchi et al 1987, Shiraga et al 1997. Because estrogen stimulates uterine epithelial cell proliferation (McCormack & Glasser 1980, Quarmby & Korach 1984 and expression of EGF, IGF-I, heparin-binding EGF-like growth factor, transforming growth factor (TGF)-and EGF-R in the reproductive tracts of mice and rats, these growth factors may mediate the estrogen-induced proliferative and differentiative responses in rodent reproductive tracts (Murphy et al 1987, DiAugustine et al 1988, Nelson et al 1991, Beck & Garner 1992, Ignar-Trowbridge et al 1992, Kapur et al 1992, Das et al 1994, Sahlin et al 1994, Zhang et al 1994, Falck & Forsberg 1996, Hom et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…In female fetuses, however, primary and essential factors which regulate cell proliferation and differentiation of the Müllerian duct have not yet been identified either in vitro or in vivo. EGF and insulin-like growth factor (IGF)-I stimulate cell proliferation in immature mouse uterine and vaginal epithelial cells in vitro (Tomooka et al 1986, Iguchi et al 1987, Shiraga et al 1997. Because estrogen stimulates uterine epithelial cell proliferation (McCormack & Glasser 1980, Quarmby & Korach 1984 and expression of EGF, IGF-I, heparin-binding EGF-like growth factor, transforming growth factor (TGF)-and EGF-R in the reproductive tracts of mice and rats, these growth factors may mediate the estrogen-induced proliferative and differentiative responses in rodent reproductive tracts (Murphy et al 1987, DiAugustine et al 1988, Nelson et al 1991, Beck & Garner 1992, Ignar-Trowbridge et al 1992, Kapur et al 1992, Das et al 1994, Sahlin et al 1994, Zhang et al 1994, Falck & Forsberg 1996, Hom et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining patterns and the results of in situ hybridization shown in this work support the concept that 24p3 expression in the uterus most likely takes place in the glandular and luminal epithelial cells of the endometrium. Because the response of endometrial epithelial cells to both E 2 and P 4 is rarely maintained under in vitro conditions (Tomooka et al 1986, Julian et al 1992, our analyses of 24p3 expression in mouse uterus during the natural estrous cycle and in the preimplantation period remain essential to investigate how ovarian steroids regulate uterine 24p3 expression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Cunha et al (1985Cunha et al ( , 1992 suggested that estrogeninduced female genital tract epithelial cell proliferation is mediated by the stroma. Estrogens cause a rapid increase in EGF of the uterus (DiAugustine et al, 19881, and EGF applied by pellet stimulated proliferation of uterine epithelial cells in vivo (Ignar-Trowbridge et al, 1992) and in vitro (Tomooka et al, 1986;Uchima et al, 1991). Therefore, expression of ER in uterine epithelial cells of neonatal mice may be mediated by EGF induced by estrogen.…”
Section: Discussionmentioning
confidence: 99%